Ileal Diverticulitis as a Cause of Right Lower Quadrant Pain: A Case Report and Review of the Literature - Jiten P. Kothadia (Shiraz University of Medical Sciences, 2015)
Introduction Small bowel diverticulitis is a rare clinical disease of the small bowel. The incidence of small bowel diverticulitis varies from 0.3 to 2.3 % in the general population. Complications of this rare clinical entity are often confused with other causes of acute abdomen such as acute appendicitis, perforated peptic ulcer, inflammatory bowel disease or ischemic bowel disease. Case Presentation We describe a 65-year-old male with a history of ileal diverticulosis who presented with acute abdomen and was subsequently found to have perforated ileal diverticulitis with abscess formation. Conclusions The case, differential diagnosis, imaging studies, complications and management of this rare clinical disease are discussed.